A case study in green chemistry: the reduction of hazardous solvents in an industrial R&D environment. Issue 10 (13th May 2022) - Dutta, Piyali; McGranaghan, Andrea; Keller, Isabelle; Patil, Yogesh; Mulholland, Nicholas; Murudi, Vikrant; Prescher, Horst; Smith, Alex; Carson, Nessa; Martin, Chris; Cox, Paul; Stierli, Daniel; et al.
Abstract : A two-year collective effort towards the reduction by 50% of the usage of 7 hazardous solvents (Green Chemistry Principle #5) within a large-scale industrial R&D organization. Abstract : The 12 Principles of Green Chemistry act as a guide for chemists for the design and synthesis of sustainable products. Adoption by chemists is essential for the transition. We chose the use of solvents (Principle #3) as an example of our commitment towards improved sustainabilty in chemical synthesis. Herein, we report on how our chemistry department – a community of ca. 300 chemists – reduced its usage by half of seven hazardous solvents over a period of two years. In this report, we provide a selection of the actions we set up to achieve our objective, as well as a few learnings observed during our journey. We hope that our example on transitioning and shifting mindsets towards a complete adoption of green chemistry principles will inspire others as well.